2012
DOI: 10.1177/1043454211432295
|View full text |Cite
|
Sign up to set email alerts
|

Pain Experience in Children With Advanced Cancer

Abstract: The children consistently reported pain. Child self-report and nurse documentation of pain differed, as did pain management among children who died compared with those who did not. Ethnicity differences in the identification and management of pain by nurses begs further study. Overall, nurses were aware of and responsive to pain and pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…Although children reported relatively low overall pain severity, significant impairment in functioning due to pain was reported in all areas (home, school, extracurricular, social, sleep) by 12-15% of children. Consistent with previous literature [7,31], the most commonly reported pain sites included the back, stomach, chest, arms, legs, and head. In terms of analgesic administration in the home setting, results revealed that children received few doses of analgesia.…”
Section: Discussionsupporting
confidence: 92%
“…Although children reported relatively low overall pain severity, significant impairment in functioning due to pain was reported in all areas (home, school, extracurricular, social, sleep) by 12-15% of children. Consistent with previous literature [7,31], the most commonly reported pain sites included the back, stomach, chest, arms, legs, and head. In terms of analgesic administration in the home setting, results revealed that children received few doses of analgesia.…”
Section: Discussionsupporting
confidence: 92%
“…In this study we used the pain AIR cycle to measure the pain management process in a variety of settings and patient types and to gain a broad understanding of how pain is managed in pediatrics across the country. While previous studies of pediatric pain management have been valuable in shedding light on the need for improvement in pediatric pain AIR rates, much of the research in this area has been limited to certain types of pain, such as procedural or postoperative; specific diagnoses; and in limited numbers and types of hospitals and units (Nissen & Dunford, ; Shrestha‐Ranjit & Manias, ; Stevens et al., ; Van Cleve, Muñoz, Riggs, Bava, & Savedra, ). There remains a gap in our knowledge of pediatric pain management practices, specifically the AIR cycle, in a broad range of unit types.…”
Section: Introductionmentioning
confidence: 99%
“…In pediatric oncology, most children can describe their symptom experiences with parental assistance. 3,4 However, when children and adolescents experience multiple symptoms as a result of their cancer and its treatment, it becomes more difficult for them to provide these self-reports. In fact, in a review of 9 studies, children's participation in their own clinical consultations ranged from 3% to 14.2% among children 6 to 12 years of age.…”
mentioning
confidence: 99%